Aproximación al envejecimiento activo y saludable a través de las prácticas de trabajo social con metodología de aprendizaje servicio - Cuesta Ruiz-Clavijo, Ana Belén; Raya Diez, Esther (Cuadernos de Trabajo Social, 2025)
The concept of ageing has evolved throughout history. The first references were to biological, health and/or employment-related approaches. Subsequently, the concept has been broadened to include comprehensive, multidimensional and cross-cutting approaches, such as Active Ageing (WHO, 2002) and Healthy Ageing (WHO, 2020).The purpose of this paper is to make visible the role of the university in the promotion of active and healthy ageing. The university, within the framework of its social responsibility, can play an important role in the optimisation of ageing, through its research, teaching and outreach functions. Service-learning (ApS) is an ideal methodology to enable the university to actively participate in its environment while strengthening meaningful learning.A study is presented on the development of projects aimed at improving the quality of life of the elderly in the curricular practices of the degree in Social Work at the University of La Rioja. A systematic review has been carried out of 445 posters that form part of the activity reports of the internships of ten academic years (2014/2015-2023/2024). Based on these, the projects were classified according to the type of service and activity carried out. We also analysed the information provided by the students with regard to their assessment of their experience in terms of learning and service. The conclusions of the study include the frequency of curricular internships with the elderly in relation to the total number of internships, as well as initiatives that promote Active Ageing and those that focus on care for the elderly in situations of vulnerability.
Keywords: active learning; pedagogical practice; ageing population; older people; teaching methodology